Active Packaging Produced by Extrusion with Shrimp Waste: Migration of Astaxanthin into Food Simulants - Sanches-Silva, A. (2013)
Introduction: Astaxanthin (3,3’-dihydroxy-β-β´-carotene-4-4´-dione), a potent antioxidant, is one of the major carotenoids in crustaceans. In the frame of the project ‘Preparation of active packaging with antioxidant and antimicrobial activity based on astaxanthin and chitosan’, a methodology for the incorporation of compounds obtained from shrimp waste in plastic matrices was developed to produce an active packaging with antioxidant properties. The aim of the present work was to develop and optimize a method to determine astaxanthin by ultra-high pressure liquid chromatography in fermented shrimp waste. Moreover, the method was also applied to determine the migration of astaxanthin from plastic films containing different amounts of shrimp waste to food simulants. Material and Methods: The method was optimized to determine astaxanthin by ultra-high pressure liquid chromatography (UHPLC) with diode array detection (DAD). The chromatographic separation was achieved using a vanguard pre-column (UPLCÒ BEH, 1.7 µm particle size) and a column (UPLCÒ BEH, 2.1 x 50 mm, 1.7 µm particle size) at 20 °C. The mobile phase was a gradient of A (dichloromethane/methanol with ammonium acetate/acetonitrile 5:20:75 (v/v)) and B (ultrapure water) with a flow rate of 0.5 mL/min. The optimized UPLC method allowed an excellent resolution of astaxanthin. The method was also evaluated in what concerns to validation parameters such as linearity, precision, limit of detection, limit of quantification and recovery. Low density polyethylene plastic films produced by extrusion with different amounts of the lipid fraction of shrimp waste were prepared and tested regarding migration into fatty food stimulants (isooctane and ethanol 95%, v/v). Results and conclusion: The proposed method to determine astaxanthin in shrimp waste is simple and has a low detection level (0.054 μg/mL). The concentration of astaxanthin found in the lipid fraction of fermented shrimp waste was 453.8 μg/g. The films produced by extrusion with the lipid fraction of the fermented shrimp waste did not originate astaxanthin migration into the tested fatty food simulants. Further studies could be made in order to evaluate the capacity of these films in protecting packed food from oxidation.